PENGARUH ASAM ASKORBAT TERHADAP KADAR TIMBAL FETUS DAN AKTIVITAS ENZIM SITOKROM P450 1A1 (CYP1A1) PADA INDUK MENCIT TERINTOKSIKASI TIMBAL - Juliana Christyaningsih; Harianto Notopuro; Win Darmanto; Diah Titik Mutiarawati (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2010)
Lead contamination occurs through air pollution and industry, enter the body through respiratory and digestive tract. High lead content will accumulate and affect adversely the cognitive function, causing neuropsychological dysfunction, encephalopathy, hyperactivity and other problems in children, disrupt the central nervous system and the immune system of children as well. This experimental research was randomized control group post-test only design. The experiment used of 27 pregnant mice, divided into three groups: negative control group, which were given distilled water, positive control group were exposed only to lead and the third group were exposed to lead and administered ascorbic acid. 25 mg/kg/day/orally neutral lead acetate was given during gestation day 7 to 16, and ascorbic acid 64 mg/kg/day/orally, started on gestation day 9 to 16. Treatment group with ascorbic acid supplementation had the lowest CYP1A1 enzyme activity compared to positive and negative control groups. This results confirmed by the molecular weight of CYP1A1 enzyme ranges 53.7 to 59.2 kDa, and the western blotting test showed the same thin band both two groups. The lowest of the average lead concentration in the head of fetal mice was found on the group of mice that treated with vitamin C. Supplementation of ascorbic acid can protect the liver and fetuses, by suspected mechanism that ascorbic acid could chelate the lead and excrete it via urine.